2011
DOI: 10.1159/000322556
|View full text |Cite
|
Sign up to set email alerts
|

Cryorecanalization of an Obstructed Bronchial Stent in a 12-Year-Old Boy

Abstract: We report a 12-year-old boy who underwent stent implantation into the left main bronchus at the age of 9.5 years for palliation of severe bronchial stenosis. He had developed complete obstruction of the stent by granulation tissue resulting in respiratory deterioration and the requirement of mechanical ventilation. The stent obstruction was treated at the age of 11.5 years by cryorecanalization. In this technique, cooling of the tip of the cryoprobe is used to induce adherence of the obstructing tissue allowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…Зонд легко извлекается сразу после окончания воздействия низких температур [19]. В отличие от лазерной реканализации с ее высокой энер-гией криореканализацию можно выполнять у пациентов со стентами, не боясь их повреждения, и при высокой концентрации кислорода в дыхательных путях [31]. У всех 7 пациентов после криореканализации отмечалось небольшое кровотечение (до 50-100 мл) из опухоли, которое было остановлено с помощью консервативных методов, включая аргоноплазменную или лазерную коа-гуляцию.…”
Section: материалы и методы результатыunclassified
“…Зонд легко извлекается сразу после окончания воздействия низких температур [19]. В отличие от лазерной реканализации с ее высокой энер-гией криореканализацию можно выполнять у пациентов со стентами, не боясь их повреждения, и при высокой концентрации кислорода в дыхательных путях [31]. У всех 7 пациентов после криореканализации отмечалось небольшое кровотечение (до 50-100 мл) из опухоли, которое было остановлено с помощью консервативных методов, включая аргоноплазменную или лазерную коа-гуляцию.…”
Section: материалы и методы результатыunclassified
“…The success, feasibility, and utility of airway cryotherapy via FB has been reported in children and adults for a variety of indications including endobronchial cryobiopsy, recanalization of obstructed bronchial stents, alleviating airway obstruction due to granulation tissue, mucus plugs, endobronchial tumors, endobronchial thrombi, plastic bronchitis, and removal of aspirated foreign bodies 3,5–13 . However, only a few studies have reported on using cryotherapy via FB in children 3,7,8,10–13 .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The success, feasibility, and utility of airway cryotherapy via FB has been reported in children and adults for a variety of indications including endobronchial cryobiopsy, recanalization of obstructed bronchial stents, alleviating airway obstruction due to granulation tissue, mucus plugs, endobronchial tumors, endobronchial thrombi, plastic bronchitis, and removal of aspirated foreign bodies. 3,[5][6][7][8][9][10][11][12][13] However, only a few studies have reported on using cryotherapy via FB in children. 3,7,8,[10][11][12][13] The European Respiratory Society statement on interventional bronchoscopy in children concluded that there are no established indications for cryotherapy in children due to the scarce literature and recommended studies to assess the utility of cryotherapy in children.…”
Section: Introductionmentioning
confidence: 99%
“…8 Restoration of airway patency using cryo has been described more frequently in children 9 and for a variety of pathologies, such as plastic bronchitis 10,11 tracheal stenosis, 12,13 and the recanalization of obstructed bronchial stents. 14 Additionally, the removal of bronchial mucoepidermoid carcinoma in six patients 15 and the debulking of an inflammatory myofibroblastic tumour 16 have been reported. Removing organic and inorganic foreign bodies using cryotherapy has successfully been reported in a study comprising 12 children 17 and in two case reports.…”
Section: Introductionmentioning
confidence: 99%
“…In adults, a recent shift towards cryobiopsy can be observed 8 . Restoration of airway patency using cryo has been described more frequently in children 9 and for a variety of pathologies, such as plastic bronchitis 10,11 tracheal stenosis, 12,13 and the recanalization of obstructed bronchial stents 14 . Additionally, the removal of bronchial mucoepidermoid carcinoma in six patients 15 and the debulking of an inflammatory myofibroblastic tumour 16 have been reported.…”
Section: Introductionmentioning
confidence: 99%